2015
DOI: 10.1007/s00404-015-3943-3
|View full text |Cite
|
Sign up to set email alerts
|

Is there an association between assisted reproductive technologies and time and complications of the third stage of labor?

Abstract: Patients who conceived after non-COH ET were at increased risk for manual placental extraction. This association was not influenced by age differences between groups. Further research must be done to determine which elements of the ART process are responsible for these differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 8 publications
2
11
0
Order By: Relevance
“…High oestradiol and progesterone concentrations, as a result of multiple folliculogenesis, may produce suboptimal angiogenesis and placentation, predisposing to PPH. Therefore, a major role may be played by ART procedures themselves, but uterine and hormonal conditions associated with infertility may contribute to the increased failed induction and postpartum complications observed (Stern et al, 2015; Healy et al, 2010; Aziz et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…High oestradiol and progesterone concentrations, as a result of multiple folliculogenesis, may produce suboptimal angiogenesis and placentation, predisposing to PPH. Therefore, a major role may be played by ART procedures themselves, but uterine and hormonal conditions associated with infertility may contribute to the increased failed induction and postpartum complications observed (Stern et al, 2015; Healy et al, 2010; Aziz et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of increased PPH after IVF, Aziz et al reported that patients who conceived after receiving oocyte donation without controlled ovarian hyperstimulation were at increased risk for manual placental extraction, and this association was not affected by age differences between groups. However, this may be only one reason for the increased PPH [37]. In addition, reactivity of the uterus to oxytocin may decrease with aging and may be a cause of bleeding [23].…”
Section: Discussionmentioning
confidence: 99%
“…The authors found a positive association between retained placenta and oocyte donation, as well as between PPH and oocyte donation 15. In another 2016 study by Aziz et al, seeking to determine whether or not length of third stage was related to IVF, the authors concluded that cryopreserved embryo transfer (donated or autologous) without controlled ovarian hyperstimulation was not related to longer third stage, but did significantly increase the risk for manual removal of the placenta 16…”
Section: Risk Factorsmentioning
confidence: 99%